2022
DOI: 10.3390/su14094889
|View full text |Cite
|
Sign up to set email alerts
|

Air-Quality Prediction Based on the EMD–IPSO–LSTM Combination Model

Abstract: Owing to climate change, industrial pollution, and population gathering, the air quality status in many places in China is not optimal. The continuous deterioration of air-quality conditions has considerably affected the economic development and health of China’s people. However, the diversity and complexity of the factors which affect air pollution render air quality monitoring data complex and nonlinear. To improve the accuracy of prediction of the air quality index (AQI) and obtain more accurate AQI data wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 45 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Accordingly, in this case, one needs to reduce the δ parameter for (9). If the time series is close to random, then the errors e n p τ τ − ( ) will increase, and, therefore, it is necessary to take them into consideration in adjusting the forecast according to the combined selective model, increasing the δ parameter for (9). The level of persistence, randomness, and anti-persistence of the time series is determined on the basis of fractal R/S-analysis.…”
Section: Discussion Of the Choice Of Parameters For The Forecasting M...mentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, in this case, one needs to reduce the δ parameter for (9). If the time series is close to random, then the errors e n p τ τ − ( ) will increase, and, therefore, it is necessary to take them into consideration in adjusting the forecast according to the combined selective model, increasing the δ parameter for (9). The level of persistence, randomness, and anti-persistence of the time series is determined on the basis of fractal R/S-analysis.…”
Section: Discussion Of the Choice Of Parameters For The Forecasting M...mentioning
confidence: 99%
“…The results of the study described in [8] showed that the EMD method can be used to improve the accuracy of the forecasting model when working with complex air quality data. Paper [9] considers the combination of models based on EMD with the model of neural networks. Neural network models require parameter adjustments to ensure the calculation of the high accuracy forecast.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…For recent decades, due to rapid urbanization and economic growth, developing countries like India are facing severe haze pollution. The World Health Organization (WHO) has stated that around 4.2 million individuals died prematurely/annum to long‐term exposure to ambient atmosphere 1 . PM2.5 is the major risk factor among all pollutants, causing more health hazards such as lung cancer, cardiovascular disease, asthma, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Four different position updating methods are used according to the different categories of individuals. Although DBO has advantages of strong global search capability, it also has disadvantages of local optimization and slow convergence due to the random distribution of initial population [21]. Scholars have made improvements to address the shortcomings.…”
Section: Introductionmentioning
confidence: 99%